Alternative Spiritualities:Different Personalities? An Enquiry Concerning Paranormal Beliefs And Traditional Religiosity - Francis, Leslie J. (Research in the social scientific study of religion, 2009)
The present study examined whether belief in the paranormal serves the same psychological functions as traditional religiosity in terms of occupying the same personality space. A sample of 659 14- to 16-year-old secondary school pupils attending four schools in England completed the short-form Junior Eysenck Personality Questionnaire together with indices of paranormal belief and of traditional religiosity. The data demonstrated that, while traditional religiosity was associated with lower psychoticism scores (tendermindedness) and higher lie scale scores (greater social conformity), paranormal belief was associated with higher psychoticism scores (toughmindedness) and lower lie scale scores (lower social conformity). These findings suggest that paranormal beliefs may be serving a somewhat different psychological function in comparison to traditional religiosity